Genomics-Guided Accelerated Improvement of Stress Tolerance in Grain Legume Crops - Bohra, Abhishek; Das, Alok; Singh, N. P. (International Journal of Economic Plants, 2016)
The current trajectory of population growth indicates that the world population is to cross 9 billion by 2050, and could likely reach 11 billion by the end of 21st century. This upward trend in turn necessitates a quantum leap in the global food production by 70% in order to meet the dietary demands of the global population. The increasing severity of the global crop looses accounted to the pest problems is reflected in the fact that the amount of yield lost to these attacks are adequate to feed almost one billion people worldwide. Pulses are generally grown on marginalized soil and risk prone environment where their production is subject to a number of yield-limiting constraints that include pests, diseases and various other agricultural adversities. Given growing concerns to agricultural sustainability and environmental safety, resistance breeding remains the most economically-viable and widely accepted strategy for developing improved crop cultivars showing markedly enhanced level of resistance to various biotic and abiotic constraints. In recent years, transformational developments in the area of legume genetics and genomics have resulted in the availability of modern genomic tools that are potentially underpinning various crop improvement schemes.